2018
DOI: 10.2174/1874210601812010080
|View full text |Cite
|
Sign up to set email alerts
|

Guided Implant Surgery to Reduce Morbidity in Von Willebrand Disease Patients: A Case Report

Abstract: Introduction:Von Willebrand Disease is the most common inherited bleeding disorder. In the general population, 1/8000 patients are affected. Primary hemostasis (platelet adhesion) and coagulation (protection of Factor VIII) are altered. Among several bleeding symptoms, these patients suffer from excessive bleeding of oral mucosa and dental management requires a close collaboration between haematologists and oral surgeons.Materials & Methods:Guided implant surgery can be used to increase the accuracy of implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There are several advantages with guided surgery: in addition to controlling the implant position, depth, and inclination [ 15 , 16 ], there is the possibility of inserting implants flaplessly [ 17 ] (i.e., without having to raise a mucoperiosteal flap). This reduces post-operative pain for the patient and it simplifies the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several advantages with guided surgery: in addition to controlling the implant position, depth, and inclination [ 15 , 16 ], there is the possibility of inserting implants flaplessly [ 17 ] (i.e., without having to raise a mucoperiosteal flap). This reduces post-operative pain for the patient and it simplifies the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This reduces post-operative pain for the patient and it simplifies the intervention. This minimally invasive approach allows the preservation of the periosteal microcirculation, with potential benefits to tissue stability [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…von Willebrand factor may be a significant modulator of implant stability, according to research by Brouwers et al 353 . Fénelon et al 354 . found that guided implant surgery enabled a minimally invasive approach and prevented patient bleeding issues.…”
Section: Discussionmentioning
confidence: 99%
“…351 There is no evidence to suggest that bleeding disorders contraindicate receiving dental implants in medically impaired individuals; however, these individuals may be at risk of blood loss and long-term bleeding. 352 von Willebrand factor may be a significant modulator of implant stability, according to research by Brouwers et al 353 Fénelon et al 354 found that guided implant surgery enabled a minimally invasive approach and prevented patient bleeding issues.…”
Section: Von Willebrand Diseasementioning
confidence: 99%
“…Among seventeen articles, twelve were case reports and five reviews. Seven articles considered patients with haemophilia [12][13][14][15][16][17][18], seven considered patients with Von Willebrand Disease [19][20][21][22], one considered patients with Idiopatic Trombocitopenic Purpura [23]. Five articles performed the surgery flapless [12,[18][19][20][21], three articles did not [13,14,17] and four articles did not specify [15,16,22,23].…”
Section: Congenital Coagulation Disorders (Ccds)mentioning
confidence: 99%